Radiographic Evaluation of Root Canal Fillings Accomplished by Undergraduate Dental Students - Yavari, Hamidreza; Samiei, Mohammad; Shahi, Shahriar; Borna, Zahra; Abdollahi, Amir Ardalan; Ghiasvand, Negar; Shariati, Gholamreza (Iranian Endodontic Journal, 2015)
Introduction: The purpose of this study was to evaluate the radiographic quality of root canal fillings by fourth-, fifth-, and sixth-year undergraduate students at Tabriz Faculty of Dentistry between 2006 and 2012. Methods and Materials: A total of 1183 root canal fillings in 620 teeth were evaluated by two investigators (and in case of disagreement by a third investigator) regarding the presence or absence of under-fillings, over-fillings and perforations. For each tooth, preoperative, working and postoperative radiographs were checked. The Pearson’s chi-square test was used for statistical evaluation of the data. Inter-examiner agreement was measured by Cohen’s kappa (k) values. The level of significance was set at 0.05. Results: Total frequencies of over-filling, under-filling and perforation were 5.6%, 20.4% and 1.9%, respectively. There were significant differences between frequencies of over- and under-fillings (P<0.05). Unacceptable quality, under- and over-fillings were detected in 27.9% of 1183 evaluated canals. Conclusion: The technical quality of root canal therapies performed by undergraduate dental students using step-back preparation and lateral compaction techniques was unacceptable in almost one-fourth of the cases.